Peace and the medical profession - R. Soewasono R. Soewasono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1986)
This article described how nuclear weapons could pose a threat to the health and life of people. An all out nuclear war would destroy world civilization, and human existence itself would be imperiled. There could be no adequate medical response to a nuclear war; the only cure is prevention. Furthermore, this article pinpointed that all physicians should be aware of their responsibilities to give aid not just to the sick but to the billions of well living human beings who comprise the human species. The easiest way to shoulder this responsibility is by working to prevent nuclear war, because of their ethical commitment to protect the life and health of humankind. Finally, the teaching about nuclear weapons and nuclear war in medical schools is proposed. Key Words: peace - nuclear war - protection of humankind - medical profession - peace—oriented education